Bentuk Tari Ittar Mulei Di Sanggar Widya Sasmita Kabupaten Lampung Tengah - Maharani, Shinta (Jurnal Seni dan Pembelajaran, 2023)
The Ittar Mulei dance is a cultural heritage dance from Central Lampung that depicts the process of releasing the bride to the groom. The research aims to describe the form of the Tari Ittar Mulei in the Widya Sasmita Studio, Central Lampung Regency. This study uses a qualitative descriptive method, collecting data through observation, interviews, and documentation. The data analysis technique is divided into three stages: reduction, presentation, and conclusion drawing. The research findings show that the elements of Tari Ittar Mulei consist of movements, musical accompaniment, makeup, costumes, props, and floor patterns. The dance has three movement parts: matek, cangget, and bedana. The musical accompaniment includes gongs, canang, drums, gujih, accordion, kulintang, rebana, and bedug. The costumes include clothes brackets, tapis cloth, kamisol, selappay tapis, bebe, belt, and bridal siger. The props used in this dance are tapis cloth, talam becaluk, and two pieces of selendang cloth. There are five floor patterns in Tari Ittar Mulei: letter A-shaped, arrow, letter V, two three two, and hexagon.Keywords: dance form, Ittar Mulei dance, widya sasmita company